Pengaruh Loose Parts Play Terhadap Pengenalan Konsep Angka Anak Usia 5-6 Tahun Di TK Mutiara Ceria Pasaman Barat - Cici Putri Utami; Delfi Eliza (JECED : Journal of Early Childhood Education and Development, 2022)
This research is motivated because by the low recognition of the concepts of number in children aged 5-6 years. The research objective is to determine the effect of loose parts play on the introdution of the concepts of number for children aged 5-6 years. This type of research uses a quasy experimental. The average result of the pre-test eksperimental class: 17,7 and post-test: 23,1. While the pre-test control class:18,6 and post-test: 22,1. For the difference in the average result of the experimental class is 5,4 and the control class is 3,5. The research as conducted for 4 weeks. The research was carried out in two classes, class B1 experimen and B2 the control class. On the hypothesis test with an independent sample t-test the sig (2-tailed) of 0,06 is less than 0,05 has an effect of 1,4. Therefore, it can be concluded that the use of loose parts play activities for the introduction of the concepts of number for children aged 5-6 years is very effective in being used in Mutiara Ceria West Pasaman.